2002
DOI: 10.1021/ac015674m
|View full text |Cite
|
Sign up to set email alerts
|

Programmable Delivery of DNA through a Nanopipet

Abstract: We report the pulsed delivery of single-stranded DNA molecules through a nanopipet. The conical geometry of the pipet leads to a localized electric field, since all of the potential drop occurs in the tip region. Pulsatile delivery of DNA molecules can be achieved in an experimentally simple way with high precision by controlling the applied voltage. Single-molecule detection and fluorescence correlation spectroscopy in the nanopipet enable us to determine the number of molecules delivered. Anomalous slow diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
100
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 86 publications
(102 citation statements)
references
References 43 publications
2
100
0
Order By: Relevance
“…Nanopipettes have recently been used to write high-resolution DNA and protein patterns on surfaces in the presence of a surrounding liquid and with the use of electrical fields to control the flow of reagents from the pipette tip to the surfaces. [312,313] Coaxial pipettes were also used for releasing neurotransmitters to a neuronal network with spatial control. [314] These two techniques are elegant but may lack versatility and convenience for a range of applications.…”
Section: Non-contact Microfluidics Operating Under a Liquidmentioning
confidence: 99%
“…Nanopipettes have recently been used to write high-resolution DNA and protein patterns on surfaces in the presence of a surrounding liquid and with the use of electrical fields to control the flow of reagents from the pipette tip to the surfaces. [312,313] Coaxial pipettes were also used for releasing neurotransmitters to a neuronal network with spatial control. [314] These two techniques are elegant but may lack versatility and convenience for a range of applications.…”
Section: Non-contact Microfluidics Operating Under a Liquidmentioning
confidence: 99%
“…We previously utilized the very high electricfield gradients generated at the tip of a nanopipette to controllably concentrate and deliver DNA. [21][22][23] The pipettes have an inner diameter of 100 nm and the voltage drop occurs in the last few microns of the tip owing to its tapered shape. By application of a potential of 1 V between the electrode in the bath and the electrode in the pipette, a very high electric field of % 8000 V cm À1 is generated at the tip of the pipette.…”
mentioning
confidence: 99%
“…The SICM nanopipette can also be used as a reservoir of analyte (e.g. DNA) that can then be delivered to a surface in a highly localized manner by controlling the bias of the QRCE in the nanopipette [16,[74][75][76][77][78]. Such studies have potential application in the delivery of particular molecules and therapeutics to a specific cell or subcellular region.…”
Section: (D) Conductance Measurements Local Delivery and Sizingmentioning
confidence: 99%
“…This approach has been used to study endocytic pathways [150], such as probing the mechanism of clathrin-coated pit closure [151]. Additionally fluorescence measurements have been very valuable in following the dynamics of delivery from nanopipettes and the behaviour of the fluorescent moieties while in a nanopipette [75,152]. These studies showed that it was possible to deliver a single fluorescent molecule to different subcellular regions of a boar spermatozoon and track the diffusion therein [152].…”
Section: (D) Scanning Electrochemical Microscopy-scanning Ion Conductmentioning
confidence: 99%